THE EFFECT OF UNUSUAL MOVINGACTIVITY ANNOUNCEMENT ON STOCK RETURN AND TRADING VOLUME IN INDONESIA STOCK EXCHANGE - Ika Yanuarti; Mulyono Mulyono (Universitas Hayam Wuruk Perbanas, 2013)
One of the information submitted by the Indonesia Stock Exchange, related to stock trading is the announcement of Unusual Market Activity (UMA). The UMA announcement is a trade activities and or price movements of unusual effect on a certain period of time which, according to the assessment on the Indonesia Stock Exchange could potentially disrupt the holding of regular stock trading, fair and efficient. This announcement does not necessarily indicate a breach in the field of capital market. Publication ofUMA announcement can be one form of protection to investors when a company's stock price has been moreover volatile. The sample of this study is the listed companies included in UMA announcement period 2011. This study uses Paired Samples T-test Analysis and Wilcoxon Signed Ranks Test. The conclusion is the stock return was affected by UMA announcement but the trading volume activity was not affected by UMA announcement.